Training to Create E-Modules Using Professional Flip PDF Application for Lecturers of PKK FT Makassar State University - Wardimansyah Ridwan; Besse Qur'ani; Ayu Saputri Bahar; Fitry Purnamasari (Faculty of Economics Universitas Sarjanawiyata Tamansiswa, 2023)
This Community Service conducted training in creating e-modules using the professional flip PDF application which was held for lecturers in the Department of Family Welfare Education, Faculty of Engineering, Makassar State University. This training aims to improve lecturers' abilities in developing and using interactive learning media based on information technology. The methods used in this training are presentations, discussions and practice in creating e-modules. Training and mentoring carried out directly by the service team is carried out with a time division of 20% for theory and 80% for practice in creating e-modules. The results of this training showed a significant increase after giving a pretest before the training started and a posttest after the training ended. And this training activity can increase participants' insight and abilities in creating e-modules using the professional flip PDF application and participants will gain satisfaction regarding the training provided by the service team. Keywords: Flip pdf professional, Training, Community Service